Caracterización del sector arrocero en Ecuador (2014-2019) Avanzando tecnológicamente - Andrade, Robert Santiago; Marín, Diego; Urioste, Sergio; Labarta, Ricardo Antonio; Castro, Marcelo; Pérez, Paulina (2020)
Results presented for the Ministry of Agriculture carachterizing rice production in Ecuador between 2014 and 2019.